ANALYSIS OF STUDENT MISCONCEPTIONS IN LEARNING BUFFER SOLUTION MATERIAL USING FOUR-TIER TEST WITH CERTAINTY OF RESPONSE INDEX METHOD - Sihite, Miranda Anggelina; Ginting, Elfrida (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2025)
This research aims to identify students' misconceptions about buffer solution material. This type of research uses a descriptive quantitative approach. The subjects in this research were 33 students from one class XI Science at SMA Negeri 1 Girsang Sipangan Bolon using a purposive sampling technique. The data analysis technique uses interpretation of the results of the four-tier diagnostic test with Certainty Response Index. Based on the results of data analysis, it is known that the percentage of misconceptions is 41%, not understanding concepts 32%, and understanding concepts 27%. The misconceptions that occur are in the medium category. The misconception profile for each buffer solution sub-material as follows: definition and properties of buffer solutions 37,6%, components of the buffer solution 42,5%, calculation of the pH value of the buffer solution 44%, and the role of buffer solutions for living things 40,6%. The biggest misconception sub-material is calculation of the pH value of the buffer solution 44%. The smallest misconception sub-material is definition and properties of buffer solutions 37,6%. The results of the research found that there are still many students who experience misconceptions, so further research needs to be carried out to identify student misconceptions in other materials.